Pandemic [compact disc, unabridged] : a novel - Cook, Robin, 1940- (Penguin Audio, 2018)
After a young, seemingly healthy woman collapses suddenly on the NYC subway and dies by the time she reaches the hospital, her case is initially chalked up to a virulent case of influenza. That is, until she ends up on Dr. Jack Stapleton's autopsy table, where Jack discovers something eerily fishy: first, that the young woman has had a heart transplant, and second, that her DNA matches that of the transplanted heart.